2006
DOI: 10.1021/jp0630572
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Potential Surface Topographies through the Distribution of Saddles and Minima

Abstract: Three related clusters of thirteen particles bound by pairwise Morse potentials with different ranges are the vehicles for relating the dynamics and kinetics of these clusters to the topographies of their energy landscapes. The analyses are based on the distributions of minima and saddles, on the asymmetries of the barriers and the kinetics of passage among the energy bands that the distributions of minima display. While all three of the examples are essentially structure-seekers, the extent of this character … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Of these structures, only 7e has been proposed elsewhere , as feasible. In fact, although structure 7a has been proposed as the GM for other binary compounds, e.g., zinc sulfide, silver iodide, and magnesium oxide, we have not found it reported by others for zinc oxide. The other structures that have already been reported as metastable include 7c and 7f (as 7h and 7f by Wang et al) and 7i (as 7b by both Maxtxain et al and Wang et al).…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…Of these structures, only 7e has been proposed elsewhere , as feasible. In fact, although structure 7a has been proposed as the GM for other binary compounds, e.g., zinc sulfide, silver iodide, and magnesium oxide, we have not found it reported by others for zinc oxide. The other structures that have already been reported as metastable include 7c and 7f (as 7h and 7f by Wang et al) and 7i (as 7b by both Maxtxain et al and Wang et al).…”
Section: Resultscontrasting
confidence: 85%
“…The ease of locating a metastable structure (local minimum) depends on the relative width of the basin within which it sits compared to its neighbors, the relative width of the superbasin containing neighboring local minima that are connected by barriers below a defined height or the basin on the relaxed landscape, and the relative width of the supersuper basin etc. Others have employed a technique for such analyses, where the landscape is drawn so that it resembles the roots of a tree, a disconnectivity graph, and from which one can see whether the landscape is likely to funnel the EA toward a local minimum or the GM. These analyses need the knowledge of the barrier heights between the local minima and are therefore beyond our present study.…”
Section: Resultsmentioning
confidence: 99%
“…Yagi et al demonstrated through in situ experiments that such shape changes could occur, later confirmed by Iijima and Ichihashi . While there were initially some questions as to the role of electron-beam heating or core excitations in the experiments, a more general explanation by Ajayan et al indicated that the activation energy for transformations between structures was relatively modest, similar to the energy landscape model for much smaller clusters developed by Berry and co-workers. Ajayan et al also speculated that there should be a size–temperature phase diagram for nanoparticles.…”
Section: Introductionmentioning
confidence: 89%
“…Evolutionary Computation Volume 20, Number 4 For the 13-atom Morse cluster, a thorough characterization of the landscape topography in function of a single parameter ρ of the Morse pair potential can be found in Cox et al (2006). Putative ground states of Morse clusters for N ≤ 80 and different ρ values are reported in the Cambridge Cluster Database (Wales et al, 2009).…”
Section: Discussionmentioning
confidence: 99%